Pengaruh Metode Praktikum IPA Berbasis Science Writing Heuristic (SWH) dan Motivasi Berprestasi Terhadap Hasil Belajar Kognitif Peserta Didik - Tri Retnosari; Nurbaity Nurbaity; Maria Paristiowati (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This research aims to analyze the effect of the applying of SWH-based experiment method and the achievement motivation of 7th-grade students toward the Science’s learning outcome in the chapter of Properties and Physical and Chemical Changes. The applied of SWH-based experiment method and achievement motivation is an approachment to support the process of learning. The research was conducted in October 2015 until June 2016 at private junior high school in Bekasi. The method of study that used is quasi-experiment with factorial design 2x2. The sample consisted of 40 students which determined by simple random sampling technique. The data of cognitive learning was measured by the learning outcome and learning motivation which determined based on the questionnaire. The gained data were distributed normally and homogeny. The data analysis result was using two-way ANAVA test, resulted: 1) the applied of SWH-based experiment method lead to an increasement of Science’s learning outcome compared to conventional method; 2) the applied of SWH-based experiment method toward student with high achievement motivation lead to a better learning outcome rather than conventional method; 3) the applied of SWH-based experiment method toward student with low achievement motivation didn’t lead to a higher of Science’s learning outcome than the applied of conventional method; 4) an interaction was found between experiment method and motivation of achievement toward the learning outcome. Keywords: Science Writing Heuristic, Achievement Motivation, Learning Outcome